2002
DOI: 10.1055/s-2002-34341
|View full text |Cite
|
Sign up to set email alerts
|

Neuronavigation and Functional MRI for Surgery in Patients with Lesion in Eloquent Brain Areas

Abstract: Functional MRI provides important additional information in patients with lesions in eloquent brain areas. In combination with neuronavigation this is a very helpful technique for surgical interventions on these patients to reduce morbidity. Nonetheless, there are still open questions concerning accuracy of display of the functional areas and integration into a neuronavigation system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 17 publications
(19 reference statements)
0
16
0
Order By: Relevance
“…However, valid clinical fMRI localizations need to be possible with every local hardware situation, and due to considerable mislocalizations in some of our patients, we conclude that automatic coregistration techniques should be evaluated carefully, especially in case of clinical application. With no doubt, such software may be useful during the preparation of clinical or non-clinical reports, but detailed control by experienced clinical fMRI professionals seems recommendable [1,2,36,37,[47][48][49]. Future research should extend evaluations of coregistration Maximum 3D distances between the reference point localizations generated by human experts are shown on the left for all 20 participants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, valid clinical fMRI localizations need to be possible with every local hardware situation, and due to considerable mislocalizations in some of our patients, we conclude that automatic coregistration techniques should be evaluated carefully, especially in case of clinical application. With no doubt, such software may be useful during the preparation of clinical or non-clinical reports, but detailed control by experienced clinical fMRI professionals seems recommendable [1,2,36,37,[47][48][49]. Future research should extend evaluations of coregistration Maximum 3D distances between the reference point localizations generated by human experts are shown on the left for all 20 participants.…”
Section: Discussionmentioning
confidence: 99%
“…Comparable to related studies [10,11,[24][25][26][31][32][33][34][35][36][37], two groups of ten participants each were recruited for this investigation. Healthy right-handed volunteers (three females and seven males; mean age: 23.9 years; standard deviation: 4.3 years) and right-handed patients (six females and four males; mean age: 41.0 years; standard deviation: 16.3 years) suffering from large brain lesions.…”
Section: Methodsmentioning
confidence: 99%
“…However, modern fusion techniques have only recently been developed. Therefore, there are little data in current literature which specifically analyzes and stratifies the clinical benefit of neuronavigation enhanced by fMRI [3,[23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…The need for definition of eloquent cortex in the individual patient led to the clinical application of BOLD imaging, which is a noninvasive method increasingly used for the presurgical evaluation. Benson et al (2) compared the laterality of language dominance determined by BOLD with those determined by Wada testing In the present study, preoperative brain mapping with BOLD individually showed the anatomical relationship of somatosensory areas to tumour in vivo, optimized operative plan and guided surgical approach in 5 patients, although we were unable to integrate these functional images into surgical navigation system which had been described in recent literatures (9,30,33).…”
Section: The Value Of Preoperative Bold In Surgical Treatment Of Braimentioning
confidence: 58%